Imaging of complex sulfatides SM3 and SB1a in mouse kidney using MALDI-TOF/TOF mass spectrometry - Marsching, Christian; Eckhardt, Matthias; Gröne, Hermann-Josef; Sandhoff, Roger; Hopf, Carsten (Analytical and bioanalytical chemistry, 2011)
Sulfatides, a class of acidic glycosphingolipids, are highly expressed in mammalian myelin and in kidney, where they are thought to stabilize neuronal structures and signaling and to influence osmotic stability of renal cells, respectively. Recently, 9-aminoacridine (9-AA) has been introduced as a negative ion matrix that displays high selectivity for low complexity galactosylceramid-I3-sulfate sulfatides and that is suitable for quantitative analysis by matrix-assisted desorption/ionization (MALDI) mass spectrometry (MS). Analyzing acidic fractions of lipid extracts and cryosections from kidneys of wild type and arylsulfatase A-deficient (ASA −/−) mice, we demonstrate that 9-AA also enables sensitive on-target analysis as well as imaging of complex lactosylceramide-II3-sulfate and gangliotetraosylceramide-II3, IV3 bis-sulfate sulfatides by MALDI-TOF/TOF MS. Utilizing the MALDI imaging MS technique, we show differential localization in mouse kidney of (1) sulfatides with identical ceramide anchors, but different glycan-sulfate head groups but also of (2) sulfatides with identical head groups but with different acyl- or sphingoid base moieties. A comparison of MALDI images of renal sulfatides from control and sulfatide storing arylsulfatase A-deficient (ASA −/−) mice revealed relative expression differences, very likely reflecting differences in sulfatide turnover of the various renal cell types. These results establish MALDI imaging MS with 9-AA matrix as a label-free method for spatially resolved ex vivo investigation of the relative turnover of sulfatides in animal models of human glycosphingolipid storage disease.